Adiwiyata: Integrating Environmental Education and PKLH-Based Sustainability into Teaching and Learning - Jamil; Hasanuddin (Postgraduate, University of Mataram, 2026)
Population and Environmental Education (PKLH) learning plays a strategic role in addressing global issues such as climate change, pollution, and ecosystem degradation. This research was conducted at SMP Negeri 1 Tinggi Moncong, Gowa Regency, over one semester of the 2024/2025 academic year. This study aims to analyze the effectiveness of integrated PKLH teaching in improving students' ecological knowledge, attitudes, and skills; to identify implementation challenges; and to evaluate the internalization of the concepts of sustainability, pollution, and conservation. This research uses a quantitative approach with a correlational design and simple regression analysis. The data collection methods in this study used four main techniques: questionnaires, interviews, observation, and documentation. The findings indicate that the integration of PKLH significantly contributes to balanced development across the cognitive, affective, and psychomotor domains, reflecting meaningful and environmentally oriented learning. However, its implementation faces obstacles, including limited environmental literacy and low student engagement in real-life ecological activities. The study concludes that the integration of PKLH has the potential to strengthen a culture of sustainable education and stimulate student participation in pro-environmental practices. Implications for schools include expanding training for school staff, ensuring environmental infrastructure support, and developing contextual learning grounded in sustainability.